2017
DOI: 10.1002/joc.5242
|View full text |Cite
|
Sign up to set email alerts
|

Changing relationship between La Niña and tropical cyclone landfalling activity in South China (La Niña and TC landfalling activity in South China)

Abstract: This study investigates the effect of El Niño–Southern Oscillation and Indo‐Pacific warm pool sea‐surface temperature (SST) on tropical cyclone (TC) landfalling activity along the South China coast and develops a scheme for predicting this activity. In general, landfalling activity tends to be suppressed in El Niño years but a large uncertainty is found for La Niña years. Landfalling activity is generally enhanced in La Niña years before 1997 but suppressed in those after 1997, which may be related to the chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…TC tracks in the WNP can be classified into different types by predefining regions under threat (Liu and Chan 2008;Wang et al 2013;Colbert et al 2015;Shan and Yu 2020b). Three prevailing types are considered in this study.…”
Section: Variation Of Prevailing Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…TC tracks in the WNP can be classified into different types by predefining regions under threat (Liu and Chan 2008;Wang et al 2013;Colbert et al 2015;Shan and Yu 2020b). Three prevailing types are considered in this study.…”
Section: Variation Of Prevailing Typesmentioning
confidence: 99%
“…It is known that most of the TCs that occur in the WNP ocean basin can be classified into a few different types according to the geometry of their tracks (Camargo et al 2007;Liu and Chan 2008;Chu et al 2010;Colbert et al 2015). Those making landfall in southern China are essentially moving straight westward whereas those making landfall in southeastern China are generally moving northwestward when approaching the coast.…”
Section: Introductionmentioning
confidence: 99%
“…6 , which shows that the majority of the annual-maximum typhoons move northwestward. Liu and Chan 33 , 34 showed that, landfalling typhoons in the South China (Guangdong and Hainan provinces) tend to be normal or below normal during El Niño years. Therefore, there are more strong typhoons making landfalls in Guangdong, Guangxi, and Hainan in non-El Niño years, which can enhance local AMTSSs therein.…”
Section: Resultsmentioning
confidence: 99%
“…It has been verified in numerous previous studies that the El Niño‐Southern Oscillation (ENSO) is a crucial factor influencing the frequency of TC genesis in the northwestern and southeastern WNP. Specifically, it is believed that TC track and landfall are closely related with the ENSO (Choi, Ha, & Jin, 2019; Kim et al., 2011; K. S. Liu & Chan, 2003, 2018; B. Wang & Chan, 2002; Zhan et al., 2018; H. Zhang & Guan, 2014; W. Zhang et al., 2012; Zhou & Lu, 2019). K. S. Liu and Chan (2003) pointed out that a strong El Niño event can reduce the frequency of TC landfall, whereas more TCs make landfall in the South China coast during La Niña years.…”
Section: Introductionmentioning
confidence: 99%